Sürekli Döküm Prosesinde Pota Nozulu Tıkanma Probleminin Analizi Ve Azaltılması - Çetin, Zafer (Fen Bilimleri Enstitüsü, 2017)
Günümüzde, kişi başına düşen çelik kullanımı ülkelerin gelişmişlik düzeylerinin bir göstergesi olarak kabul edilmektedir. Çeliğin kullanıldığı ilk günden bugüne kadar geçen sürede her dönem çeliğe olan ihtiyaç ve talep artış göstermiştir. Bu durumun doğal bir sonucu olarak insanoğlu çeliğin yüksek miktarlarda üretimine odaklanmış ve 60’lı yıllardan itibaren büyük bir gelişim gösteren sürekli döküm prosesi yüksek üretim hızlarına ulaşılabilmesi adına günümüzde çelik üretim prosesinin vazgeçilmez bir parçası olmuştur. Sürekli döküm prosesi, sıvı çeliğin potalar vasıtasıyla sürekli döküm taretine yerleştirilmesi ve potadan tandişe pota ara tüp vasıtasıyla, tandişten kalıba daldırma nozulu vasıtasıyla kontrollü bir şekilde akışını sağlamak suretiyle belirli bir salınım hareketiyle (sinüzoidal ve/veya non-sinüzoidal olarak) hava ve suyla (air-mist) soğutularak sıvı formdan katı forma (slab, kütük vb.) dönüştürülmesi işlemlerini kapsamaktadır. Sürekli döküm prosesinde sıvı çeliğin potadan tandişe aktarılması esnasında, pota iç nozulunda zaman zaman tıkanma problemi yaşanabilmektedir. Tıkanma esnasında nozul çapı daralmakta, çelik akışı yavaşlamakta ve en nihayetinde çelik akışı tamamen kesilmektedir. Bu durum özellikle alüminyum ile deokside edilmiş düşük karbonlu (0,03 – 0,07 %C) çeliklerde yüksek oranda görülmektedir. Sürekli döküm prosesinde pota nozulunun tıkanması kaynaklı akış kesilmesi, proses verimini ve çelik kalitesini etkileyen önemli bir problemdir. Pota nozulu tıkanmasına neden olan başlıca faktörler, çelik sıcaklığı, dizayn parametreleri (tesis, pota, nozul vb.) ve çelik temizliğidir. Bu çalışmada, çelik temizliği kaynaklı pota iç nozulu tıkanma probleminin kaynağının belirlenmesi ve problemin azaltılmasına yönelik yapılan incelemeler ve uygulamalar yer almaktadır. Çalışma Türkiye’deki bir demir-çelik tesisinde alüminyum ile deokside edilmiş düşük karbonlu çelikler üzerinde gerçekleştirilmiştir. Bahsi geçen çelik grubu sürekli döküm prosesinde en sık nozul tıkanma problemi ile karşılaşılan çelik grubu olup, problemin kök nedenini tespit etmeye ve problemin azaltılmasına yönelik incelemeler ve deneyler yapılmıştır. Bu kapsamda, düşük karbonlu çelikler grubunda nozul tıkanması meydana gelen durumlar analiz edilmiştir. Pota iç nozullarında katılaşan çelikten numuneler alınmış ve alınan numuneler üzerinde kimyasal analizler ile optik mikroskop incelemeleri ve elektron mikroskobu incelemeleri yapılmıştır. Laboratuvar incelemelerinde özellikle nozul duvarına yakın bölgelerde çelik iç yapısında yoğunlukla metalik olmayan Al2O3 tipindeki inklüzyonlar tespit edilmiştir. Ayrıca bu çalışmada aşağıda belirtilen çelik üretim prosesi parametrelerinin çelik temizliğine olan etkilerinin incelenmesi amacıyla Minitab 17 istatiksel veri analizi yazılımı vasıtası ile ikili regresyon analizleri gerçekleştirilmiştir. • Pota fırınında %P artışı • Pota fırınında kükürt giderme miktarı • Pota fırınında briket Al ilavesi • Pota ara tüp argon basıncı • Pota fırını başlangıç %S miktarı • Pota fırını alttan karıştırma süresi • Pota fırını üstten karıştırma süresi • Pota fırını işlem süresi • Pota fırını granüle Al ilave miktarı • Pota fırını son %Al miktarı • Pota fırını kireç ilave miktarı • BOF’tan potaya dökümde kireç ilave miktarı • Pota fırını son çelik sıcaklığı • Cürufta FeO+MnO miktarı • Cürufta Al2O3 miktarı • BOF’tan potaya döküm anında ön deoksidasyon işlemi • BOF üfleme sonu %C miktarı Belirlenen parametrelerden işletme koşullarında kontrol edilebilir olanlar ile deney tasarımı çalışması yapılarak bir deney seti oluşturulmuş ve bu kapsamda işletme koşullarında 80 adet deney gerçekleştirilmiştir. Laboratuvar incelemeleri, veri analizleri ve deney tasarımı çalışmaları sonucunda çelik temizliğini arttıracak en ideal koşullar belirlenmiştir. Pota fırınında cüruf deoksidasyonu yapılması, çelikte nihai %Al içeriğinin düşük tutulması, pota fırınında işlem süresinin uzun olması ve pota fırınında S giderme oranının düşük olması gibi çelik temizliğine olumlu etkileri olan parametreler uygulamaya koyularak işletme koşullarında 2100 adet döküm takip edilmiştir. Çalışma öncesinde düşük karbonlu çelikler grubunda %6,4 olan nozul tıkanma oranı , bu çalışma kapsamında gerçekleştirilen çelik temizliğini arttırmaya yönelik uygulama ve analiz değişiklikleri ile %2,5 oranına gerileyerek %60 oranında iyileşme sağlandığı belirlenmiştir.

Methods for manufacturing steel have evolved significantly since industrial production began in the late 19th century. Modern methods, however, are still based the same premise as the Bessemer Process, namely, how to most efficiently use oxygen to lower the carbon content in iron. Today, steel production makes use of both recycled materials, as well as the traditional raw materials, such as iron ore, coal, and limestone. Two processes; basic oxygen steelmaking (BOF) and electric arc furnaces (EAF) account for virtually all steel production. Continuous casting is the important linking process between steelmaking and rolling. As early as 1856, Henry Bessemer suggested a continuous casting method but just during the 1930s and 1940s continuous casting became a common production method for nonferrous metals and later from the 1960s for steels. The relatively low thermal conductivity of steel and the high casting temperatures meant that many problems had to be solved compared to nonferrous casting. In the mid-1980s, continuous casting grew into the biggest casting method, exceeding the conventional ingot steel casting route. In the ingot casting route, individual molds are filled with molten steel to produce steel ingots. The continuous casting method has a lot of benefits compared to the older ingot casting methods. The major advantages are improvement of steel quality, better yield, and savings of energy and manpower. Today, about 95% of the world’s steel production is made by continuous casting and a great number of steel qualities are cast in very wide variety of dimensions. The continuous casting process has a simple principle. The liquid steel in a ladle is transferred to the casting machine. When the casting operation starts, the nozzle at the bottom of the ladle is opened and the steel flows at a controlled rate into the tundish and from the tundish through a submerged entry nozzle (SEN) into one mold or several molds. The molds are generally water-cooled copper molds. The first solidification takes place at the metal/mold interface. The thickness of the solidified shell increases progressively when it is withdrawn through the machine. At the mold exit, the shell must be thick enough to support the liquid pool. Below the mold, the shell is cooled by spraying water. The mold cooling is called the primary cooling and the spray cooling the secondary cooling. At the machine end, the strand is cut off and transferred to a rolling mill. During steel pouring at continuous casting process the buildup of solid or semi-solid material on a refractory surface can cause nozzle clogging problem, as it effects the stream and reduce the flow rate. Thus nozzle clogging can give rise to both quality and productivity problems. Nozzle clogging is a crucial problem effecting process efficiency and steel quality. Main factors causing nozzle clogging are steel temperature, design parameters and steel cleanliness. The presence of solidified steel is clearly a problem of heat transfer. Buildups where the majority of the clog is solidified steel should be referred to as thermal clogs. Buildups due to the precipitation and/or agglomeration of solids on refractories at steelmaking temperatures should be referred to as inclusional clogs. The combination of thermal and inclusional clogging, is also possible, and many clogs contain solidified metal. The most commonly observed clogging material is alumina due to the high percentage of steel that is solely aluminium killed. Especially, low carbon (LC) steel grades are prone to nozzle clogging because of higher oxygen potential In this study, ladle nozzle clogging problem in aluminium killed low carbon steel (0,03 – 0,07 %C) grades was investigated from the point of steel cleanliness. In order to determine the main causes of nozzle clogging, laboratory investigations were performed on ladle nozzle deposit. In this scope, various samples were taken from different regions of solid steel block and optical microscopy, SEM-EDS and optical emission spectrometry analysis were implemented. During examinations, it was seen that too much inclusions in regions close to nozzle wall and inclusions were characterised with the SEM-EDS and OES analysis. According to results, there were generally Al2O3 type inclusions at nozzle deposits and it was understood that nozzle clogging was related with steel cleanliness. Steelmaking process conditions and operational parameters effect the steel cleanliness. To specify the efficient parameters, binary logistic regression analyses were executed for low carbon steel grades. The following factors were analysed with Minitab 17 statistical software and correlation with nozzle clogging were determined for each one. • P% pick up at LF • Desulphurisation ratio at LF • Addition of Al at LF • Ladle shroud Ar pressure • LF first S% content • Bottom stirring time at LF • Top stirring time at LF • Total process time at LF • Granule Al addition amount at LF • LF last %Al content • Amount of lime addition at LF • Amount of lime addition during tapping • Final steel temperature at LF • FeO% + MnO% content at LF slag • Al2O3% content at LF slag • Pre-deoxidation with coke during tapping • BOF end blow C% content The manageable process parameters were selected, which were LF last %Al content, Granule Al addition amount at LF and Ladle shroud Ar pressure to create a test set for design of experimental (DOE) method. In this scope, 80 experimental works were planned and performed at steelmaking process. According to the laboratory investigations, data analyses and DOE results, optimum process parameters were determined. With the changes of some operational practice and chemical specification long term trials were implemented and it was seen that clogging problem was decreased in 60% ratio. Consequently, nozzle clogging problem can be reduced significantly for aluminium killed low carbon steel grades with the steel cleanliness increasing practices which are summarized below. • Aluminium content should be minimized in steel • End blow C% content should be maximized for low soluble oxygen • Maximum S% level should be increased • Pre-deoxidation should be applied during tapping • Slag deoxidation should be applied • Ladle shroud Ar pressure should be minimum 0,04 bar • Desulphurization should not be applied at LF • Deoxidation should be completed at tapping • LF first S% content should be minimum • Bottom stirring time should be as long as possible • Top stirring time should be as short as possible • LF total process time should be long • Required lime addition should be supplement during taping • FeO% + MnO% content at slag should be minimum • Al2O3% content at slag should be optimized for inclusion removal
Reducing Of Ladle Nozzle Clogging Problem In Continuous Casting Process
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2016
Keywords: Oksijenli Çelik Üretim; Sürekli Döküm; Çelik Temizliği; Nozul Tıkanması; Oxygen Steelmaking; Continuous Casting; Steel Cleanliness; Nozzle Clogging